Analisis Kepemimpinan Dan Disiplin Terhadap Kinerja Pegawai Di Kecamatan Tembelang - Nina Wahyuning Tyas; Abu Talkah (Otonomi, 2022)
This study aims to see whether there is an influence between leadership and discipline on employee performance in Tembelang District. This study uses quantitative research methods with the independent/independent variables are Leadership and Discipline, while the dependent/bound variable is Employee Performance. The research location is at the Tembelang District Office, Jombang Regency with the research time in July and August 2021. In this study the sample taken was all Tembelang District employees totaling 30 people consisting of 22 civil servants, 6 honorary staff, 1 cleaning staff and Guard 1 person. The research data analysis method used is Multiple Linear Regression with technical descriptive analysis, classical assumption test, t test, f test and coefficient of determination. The results showed that Leadership had a positive and significant effect on employee performance in Tembelang District, Discipline had a positive and significant effect on employee performance in Tembelang District and Leadership and discipline simultaneously had a positive and significant effect on employee performance in Tembelang District.